2017
DOI: 10.2981/wlb.00304
|View full text |Cite
|
Sign up to set email alerts
|

Age Estimation of Live Arctic FoxesVulpes lagopusBased on Teeth Condition

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
3
21
1
Order By: Relevance
“…Among all features related to external morphology, the single best predictor of age after juvenile stage (≥1 year) was tooth attrition, which is consistent with other minimally invasive aging studies using known-age individuals (Chevallier et al, 2017;Delahay et al, 2011;Galbany et al, 2018;Gipson et al, 2000;Stander, 1997). Wild sea otters are primarily susceptible to dental attrition from foraging on hard-shelled invertebrates (Fisher, 1941;Kenyon, 1969;Winer, Liong, & Verstraete, 2013), many which burrow in sand.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Among all features related to external morphology, the single best predictor of age after juvenile stage (≥1 year) was tooth attrition, which is consistent with other minimally invasive aging studies using known-age individuals (Chevallier et al, 2017;Delahay et al, 2011;Galbany et al, 2018;Gipson et al, 2000;Stander, 1997). Wild sea otters are primarily susceptible to dental attrition from foraging on hard-shelled invertebrates (Fisher, 1941;Kenyon, 1969;Winer, Liong, & Verstraete, 2013), many which burrow in sand.…”
Section: Discussionsupporting
confidence: 85%
“…where L(t) is the predicted length at age t, L oo is the population mean asymptotic length, k is a growth parameter of dimension time −1 , and t 0 is the age at length = 0, or (-) gestation. The VBGF is a robust tool for modeling age to size relationships (i.e., mass, length, and girth) across multiple taxa of marine vertebrates (Estess et al, 2014;Garde, Heide-Jørgensen, Hansen, Nachman, & Forchhammer, 2007;Nielsen et al, 2016;Van Houtan, Andrews, Jones, Murakawa, & Hagemann, 2016), including sea otters (Laidre et al, 2006;Palomares & Pauly, 2008;Tinker et al, 2013Tinker et al, , 2017 3-year maximum error is consistent with other studies quantifying the precision of aging carnivores from tooth wear only (Chevallier et al, 2017;Galbany et al, 2018;Gipson et al, 2000).…”
Section: Von Bertalanffy Growth Functionssupporting
confidence: 82%
“…We have shown that this approach is well applicable to lynx, as we obtained a high classification accuracy for both sexes (93% in females, 92% in males); this was even higher than in marmots (81%; Karels et al 2004). These proportions of animals correctly classified by CART analysis are among the highest compared to other non-invasive, standardised ageing methods across wild terrestrial mammal species (Garshelis 1984, Gipson et al 2000, Høye 2006, Olifiers et al 2010, Chevallier et al 2017. However, since we tested the classification trees on the lynx that were included in the model construction, the accuracy of our trees might be overestimated.…”
Section: Classification Treesmentioning
confidence: 95%
“…In parallel to conservation measures, numerous studies have been carried out on the lynx life history in various areas in Europe, and health surveillance programmes have been implemented (Wölfl et al 2001, Ryser-Degiorgis et al 2005, Molinari-Jobin et al 2012, Breitenmoser et al 2016. Knowledge of the age of individual animals is crucial to perform ecological studies, investigate disease epidemiology and successfully implement conservation strategies (Stander 1997, Gipson et al 2000, Karels et al 2004, Ryser-Degiorgis 2013, Chevallier et al 2017. So far, the age of Eurasian lynx has been either roughly estimated or determined by counting cementum annuli, which is an invasive and costly method that cannot provide immediate results.…”
mentioning
confidence: 99%
“…Exceeding the safety factors that lead to tooth breakage is not common (Van Valkenburgh, 1988), indicating morphological and behavioral adaptations tend to prevent it, but the abrasion of teeth is less preventable on an individual level in carnivorans and is so constant a pressure that the metric can be used to age carnivorans in the field (e.g., White and Belant, 2016;Chevallier et al, 2017). Binder and Van Valkenburgh (2000) observed that in hyenas, there is a shift in tooth use with age from mesial deciduous premolars to distal adult premolars.…”
Section: What Does the Timing Of Tooth Eruption Tell Us About Hyainaimentioning
confidence: 99%